In Vitro Sensitivity Study Of Antifungal Drugs And Plant Extracts Against Mycotic Mastitis Cases - Sukumar , K. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A comparative study was made to find out the in vitro antifungal susceptibility of fungal isolates to commercially available antifungal drugs and plant extracts. The sensitivity was studied by disc diffusion method. Out of the three essential oils, cinnamon leaf at 1 in 10 dilution showed better in vitro antifungal activity to all the yeast and yeast like fungal organism compared to Amphotericin.B, Fluconazole and Griseofulvin. Geotrichum candidum was found to be more amenable to cinnamon leaf oil than all the commercial antifungal agents except Nystatin.